Is there an App for that? The impact of community knowledge workers in Uganda - Van Campenhout, Bjorn (International Food Policy Research Institute, 2013)
Rapidly increasing mobile phone coverage, cheaper technology, and an open platform that allows for the development of applications that extend the use of mobile devices provide new ways to reach farmers in isolated places. We investigate the impact of an intervention that uses information and communication technology devices to provide real-time agricultural information and extension services in Uganda. Using a difference-in-differences setup, we find that the introduction of this technology through a network of community knowledge workers induce farmers to adapt their crop portfolio, moving away from low-risk, low-value crops toward more commercially oriented commodities.